The Role of Ministers in Community Development The DRCA OFS as a Case Study - Pali, K. J. (2019)
The Dutch Reformed Church in Africa, Orange Free State (DRCA OFS), is one of the Dutch Reformed family of churches2 in South Africa established in 1910 for black South Africans. The analysis of the DRCA OFS mission and diaconial ministry reveals that the mission in the DRCA OFS is declining, that community projects are used to address mainly immediate needs, and that there are no strategies to address urgent social challenges in society. In the light of this, the article intends to analyse the role of DRCA OFS ministers in community development in South Africa. The leading research question is: To what extent are DRCA OFS ministers involved in community development in South Africa?